Dynamic legislative policy making under adverse selection - Vincent Anesi (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2018)
This paper develops a dynamic model of legislative policy making with evolving, privately observed policy preferences. Our goal is to find conditions under which decision rules, which assign feasible policies based on the legislators' preferences, are sustainable in the long run. We show that under some mild conditions, every decision rule that would be implementable with monetary transfers can be approximately sustained in a perfect Bayesian equilibrium of the dynamic model. In this equilibrium, the legislators receive payoffs arbitrarily close to those they would obtain if they could commit ex ante to truthfully apply the decision rule in every period. An application of our result yields a dynamic issue-by-issue median voter theorem in the vein of Baron's (1996) for a spatial framework with incomplete information.
Keywords: D71; D72; D78; 330; Committee voting; Information; Legislative bargaining; Sustainability